Caatinga plants: Natural and semi-synthetic compounds potentially active against Trichomonas vaginalis. Issue 9 (1st May 2016) - Vieira, Patrícia de Brum; Silva, Nícolas Luiz Feijó; da Silva, Gloria Narjara Santos; Silva, Denise Brentan; Lopes, Norberto Peporine; Gnoatto, Simone Cristina Baggio; da Silva, Márcia Vanusa; Macedo, Alexandre José; Bastida, Jaume; Tasca, Tiana
Graphical abstract: Abstract: Trichomonas vaginalis causes trichomoniasis; the most common but overlooked non-viral sexually transmitted disease worldwide. The treatment is based at 5′-nitroimidazoles, however, failure are related to resistance of T. vaginalis to chemotherapy. Caatinga is a uniquely Brazilian region representing a biome with type desert vegetation and plants present diverse biological activity, however, with few studies. The aim of this study was to investigate the activity against T. vaginalis of different plants from Caatinga and identify the compounds responsible by the activity. A bioguided fractionation of Manilkara rufula was performed and four major compounds were identified : caproate of α-amyrin (1b ), acetate of β-amyrin (2a ), caproate of β-amyrin (2b ), and acetate of lupeol (3a ). In addition, six derivatives of α-amyrin (1 ), β-amyrin (2 ) and lupeol (3 ) were synthesized and tested against the parasite. Ursolic acid (5 ) reduced about 98% of parasite viability after 2 h of incubation and drastic ultrastructural alterations were observed by scanning electron microscopy. Moreover, 5 presented high cytotoxicity to HMVII and HeLa cell line and low cytotoxicity against Vero line at 50 μM (MIC against the parasite). Metronidazole effect against T. vaginalis resistant isolate was improved when in association with5 .